Injury response checkpoint and developmental timing in insects - Hackney, Jennifer F (Fly (Austin), 2015)
In insects, localized tissue injury often leads to global (organism-wide) delays in development and retarded metamorphosis. In Drosophila, for example, injuries to the larval imaginal discs can retard pupariation and prolong metamorphosis. Injuries induced by treatments such as radiation, mechanical damage and induction of localized cell death can trigger similar delays. In most cases, the duration of the developmental delay appears to be correlated with the extent of damage, but the effect is also sensitive to the developmental stage of the treated animal. The proximate cause of the delays is likely a disruption of the ecdysone signaling pathway, but the intermediate steps leading from tissue injury and/or regeneration to that disruption remain unknown. Here, we review the evidence for injury-induced developmental delays, and for a checkpoint or checkpoints associated with the temporal progression of development and the on-going efforts to define the mechanisms involved.